2019
DOI: 10.20517/2394-5079.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Advances in surface markers of liver cancer stem cell

Abstract: Liver cancer stem cells (LCSCs), a small subpopulation that constitutes liver cancer heterogeneity, play a vital role in cancer initiation, invasion, recurrence, metastasis, and resistance to chemo-radiotherapy. It is believed that therapies targeting LCSCs can improve the efficacy of conventional chemotherapy and radiotherapy by completely eliminating tumors while preventing recurrence. Therefore, during last decades, numerous surface markers for LCSCs have been identified and characterized in many subtypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 181 publications
(272 reference statements)
0
3
0
1
Order By: Relevance
“…In fact, many of the liver CSC markers identified in HCC are oncofetal markers shared by hepatoblasts and hepatic progenitor cells. Our current knowledge of liver CSC cell surface markers including CD133, CD44, CD24, EpCAM, CD90, CD13, CD47, ICAM-1, LGR5 and calcium channel α2δ1; drug efflux markers including Side Population (SP), ABCB5 and aldehyde dehydrogenase (ALDH); as well as intracellular marker like keratin 19 (K19) have been comprehensively elsewhere 3,4 and summarized in Table 1.…”
Section: Markers Of Cancer Stem Cells In Hccmentioning
confidence: 99%
“…In fact, many of the liver CSC markers identified in HCC are oncofetal markers shared by hepatoblasts and hepatic progenitor cells. Our current knowledge of liver CSC cell surface markers including CD133, CD44, CD24, EpCAM, CD90, CD13, CD47, ICAM-1, LGR5 and calcium channel α2δ1; drug efflux markers including Side Population (SP), ABCB5 and aldehyde dehydrogenase (ALDH); as well as intracellular marker like keratin 19 (K19) have been comprehensively elsewhere 3,4 and summarized in Table 1.…”
Section: Markers Of Cancer Stem Cells In Hccmentioning
confidence: 99%
“…Nearly 20 molecular markers have been identified to isolate and characterize LCSCs 52 . Other studies have summarized LCSC surface markers in detail 13,[52][53][54][55] . Surface markers, such as CD13, CD44, EpCAM, CD90, CD24, CD34, CD47, ICAM1, EpCAM, LGR5, and OV6, are widely recognized as markers of LCSCs, because of their association with proliferative capacity, self-renewal capacity, drug resistance, and recurrence of liver cancer.…”
Section: Characteristics Of Lcscsmentioning
confidence: 99%
“…As the spheroids were AFP-positive tumor cells, fresh CAF isolates from 3 HCC patients were analyzed by fluorescence-activated cell sorting (FACS) for contaminating non-CAF cells (Table 1). In the three CAF isolates from HCC derived from patient 1-3 cancer stem cells (CSC) positive for CD13 [48,49], CD44, CD90 [49], CD133 [50], OV6 [49], epithelial cells or CSCs positive for EpCAM [49], or general tumor cells positive AFP [51] were identified by immunofluorescence. This confirmed that the CAF isolates still contained different amounts of contaminating cells, especially varying concentrations of CSC.…”
Section: Tumor Cells In Caf Isolationsmentioning
confidence: 99%